Tom Swift and His Submarine Boat; Or, Under the Ocean for Sunken Treasure - Appleton, Victor (Salt Lake City, UT : Project Gutenberg, 1997)
"Tom Swift and His Submarine Boat; Or, Under the Ocean for Sunken Treasure" by Victor Appleton is a novel published by Grosset & Dunlap. When Tom learns of a sunken ship carrying $300,000 in gold bullion off Uruguay's coast, he convinces his father to pursue the treasure instead of competing for a government prize. But a rival submarine follows close behind, determined to steal the fortune. Tom must navigate treacherous waters, escape foreign captivity, and dive to extreme depths to claim the sunken treasure first. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tom_Swift_and_His_Submarine_Boat
Release date is 1997-06-01
Produced by Anthony Matonac
Keywords: Science fiction; Treasure troves -- Juvenile fiction; Submarines (Ships) -- Juvenile fiction; Swift, Tom (Fictitious character) -- Juvenile fiction